Assessment of Drug-Induced QTc Prolongation in Mental Health Practice: Validation of an Evidence-Based Algorithm - Zolezzi M; Elhakim A; Qubaiah IA; Mahmoud DE; Homs S; Elamin W; Tawfik ES; Abdallah O; Eltorki Y; Al-Khuzaei N (Dove Medical Press, 2023)
Monica Zolezzi,1,* Athar Elhakim,2,* Iman A Qubaiah,1,* Doaa Elsayed Mahmoud,1,* Shorouq Homs,1,* Waad Elamin,1,* Engy Sherif Tawfik,1,* Oraib Abdallah,3,* Yassin Eltorki,3,* Noriya Al-Khuzaei3,* 1College of Pharmacy, QU Health, Qatar University, Doha, Qatar; 2College of Health Sciences, University of Doha for Science and Technology, Doha, Qatar; 3Pharmacy Department, Mental Health Services, Hamad Medical Corporation, Doha, Qatar*These authors contributed equally to this workCorrespondence: Monica Zolezzi, College of Pharmacy, QU Health, Qatar University, Doha, Qatar, Tel +974 4403 5623 (GMT +3hrs), Email mzolezzi@qu.edu.qaBackground: Drug-induced QTc interval prolongation (QTcIP) can lead to serious consequences and is often a concern for mental health practitioners, as access to experts such as cardiologists, for consultation is time-limiting and can delay treatment decisions. This research aimed at validating the content of an algorithm for the assessment, management and monitoring of drug-induced QTcIP in mental health practice.Methods: Following an initial face validity by content experts, a cross-sectional survey of mental health care practitioners with a 4-point Likert-type scale was used to assess the validity of the decision steps on the QTcIP algorithm (QTcIPA) by estimating the content validity index (CVI) and the modified kappa statistic (κ*). Participants' open-ended comments were also thematically analyzed.Results: Mental health practitioners found the QTcIPA to be appropriate, safe, and evidence-based, as indicated by the high individual item CVI scores ranging from 0.89 to 1 for all of the steps/decision statements in the three domains assessed: appropriateness, safety and reliability of the references used. Five themes emerged from the qualitative analysis of the open-ended comments, of which three were identified as strengths, including practical usability, reliable references and beneficial for pharmacists. Two themes were recognized as limitations, namely, the need for additional clinical content and application barriers.Conclusion: These results suggest that the QTcIPA may be a useful tool for mental health clinicians at the time of prescribing medications with potential risk of QTcIP. Future research will explore the implementation of the QTcIPA into clinical practice using computerized decision support tools through web-based and mobile applications.Keywords: drug-induced arrhythmias, QTc interval prolongation, algorithm, mental health practice, clinical decision tool